Risk factors for incident diabetic polyneuropathy in a cohort with screen-detected type 2 diabetes followed for 13 years: ADDITION-Denmark - Andersen, Signe Toft; Witte, Daniel R.; Dalsgaard, Else-Marie; Andersen, Henning; Nawroth, Peter Paul; Fleming, Thomas; Jensen, Troels M.; Finnerup, Nanna B.; Jensen, Troels S.; Lauritzen, Torsten; Feldman, Eva L.; Callaghan, Brian C.; et al. (Diabetes care, 2018)
OBJECTIVE To study incident diabetic polyneuropathy (DPN) prospectively during the first 13 years after a screening-based diagnosis of type 2 diabetes and determine the associated risk factors for the development of DPN. - RESEARCH DESIGN AND METHODS We assessed DPN longitudinally in the Danish arm of the Anglo-Danish-Dutch study of Intensive Treatment of Diabetes in Primary Care (ADDITION) using the Michigan Neuropathy Screening Instrument questionnaire (MNSIQ), defining DPN with scores ≥4. Risk factors present at the diabetes diagnosis associated with the risk of incident DPN were estimated using Cox proportional hazard models adjusted for trial randomization group, sex, and age. - RESULTS Of the total cohort of 1,533 people, 1,445 completed the MNSIQ at baseline and 189 (13.1%) had DPN at baseline. The remaining 1,256 without DPN entered this study (median age 60.8 years [interquartile range 55.6; 65.6], 59% of whom were men). The cumulative incidence of DPN was 10% during 13 years of diabetes. Age (hazard ratio [HR] 1.03 [95% CI 1.00; 1.07]) (unit = 1 year), weight (HR 1.09 [95% CI 1.03; 1.16]) (unit = 5 kg), waist circumference (HR 1.14 [95% CI 1.05; 1.24]) (unit = 5 cm), BMI (HR 1.14 [95% CI 1.06; 1.23]) (unit = 2 kg/m2), log2 methylglyoxal (HR 1.45 [95% CI 1.12; 1.89]) (unit = doubling), HDL cholesterol (HR 0.82 [95% CI 0.69; 0.99]) (unit = 0.25 mmol/L), and LDL cholesterol (HR 0.92 [95% CI 0.86; 0.98]) (unit = 0.25 mmol/L) at baseline were significantly associated with the risk of incident DPN. - CONCLUSIONS This study provides further epidemiological evidence for obesity as a risk factor for DPN. Moreover, low HDL cholesterol levels and higher levels of methylglyoxal, a marker of dicarbonyl stress, are identified as risk factors for the development of DPN.